Leaks in Spending - Josephine Turner (EDIS, 2003)
Budgets leak for many reasons. Learning to recognize some of the reasons may help you plug the leaks. This document is FCS5244, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, IFAS, University of Florida. Publication: December 2002.